An electric energy meter seal structure with an optical anti-counterfeiting mark and a design and preparation method thereof
Patent Information
- Application Number
- CN202611106853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-24
AI Technical Summary
[0004]目前,现有技术中利用光学薄膜实现防伪功能时仍面临一些关键困难
(1)高隐蔽性:本发明通过多层膜结构(由过渡层、功能层、保护层构成)与标识的组合,实现了极高的观测隐蔽性。在常规观测方式下(即任意观测俯仰角及非偏振光照射条件),多层膜结构的颜色与基底颜色(粉色)完全一致,关键动态光学信息完全隐藏,无法通过肉眼或普通拍摄设备识别与复制。仅在特定的观测俯仰角(50°-80°)与特定的偏振角(50°-115°和115°-150°)范围内,多层膜结构才分别呈现淡金色与紫色,从而凸显出标识的图案。这一特性有效杜绝了数码翻拍、复印等传统伪造手段,将防伪特征从“可见”提升至“可控可见”,显著增强了防伪的主动性与保密性。
Smart Images

Figure CN122618876B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electricity meter sealing technology, and relates to an electricity meter sealing structure with optical anti-counterfeiting mark and its design and preparation method. Background Technology
[0002] Electricity meter seals are anti-tampering devices installed on key parts of the electricity meter (such as terminal covers or the meter casing). They typically employ physical latches or plastic shell structures. Their core function is to prevent unauthorized opening and tampering, thereby ensuring the accuracy and fairness of electricity metering results and preventing electricity theft. Currently widely used traditional seal structures are simple in structure and have weak anti-counterfeiting capabilities, making them easy to imitate or destroy. This poses significant risks and efficiency bottlenecks to metering management, electricity bill auditing, and electricity bill collection.
[0003] To enhance the security of seals, anti-counterfeiting technologies such as self-locking snap-fit structures (Chinese invention patent CN219676116U, a type of electricity meter seal) and fluorescent fiber anti-counterfeiting (Chinese invention patent CN120082085A, a multi-layer optically variable ultraviolet fluorescent anti-counterfeiting film and its preparation method) have emerged, which have improved the concealment and tamper resistance of seals to a certain extent. However, these technologies still have certain limitations: for example, while self-locking snap-fit structures have a one-time locking characteristic, they lack concealment, and high-precision tools (such as micro angle grinders) can locally cut the locking parts, bypassing the physical anti-tampering mechanism and causing damage; fluorescent fiber filaments have a certain degree of concealment under normal conditions, but fluorescence decay occurs under long-term ultraviolet irradiation, causing the anti-counterfeiting features to gradually fail, and the color change is relatively monotonous. Therefore, developing an electricity meter sealing technology that combines high concealment, angle dependence, long-term cycle stability, and diverse color changes has become an urgent need in power system operation and maintenance.
[0004] Currently, existing technologies for achieving anti-counterfeiting functions using optical thin films still face several key challenges. First, conventional anti-counterfeiting films often fail to maintain consistent color with the sealing substrate, resulting in insufficient concealment under normal visual conditions and easy detection or imitation. Second, most optically variable films can only switch between two colors under specific conditions, with a narrow color change range and limited contrast, weakening the recognizability and anti-counterfeiting capabilities of the anti-counterfeiting features. Furthermore, the polarization response angle of these films is typically relatively uniform, further limiting their reliable identification under multi-angle and complex lighting conditions. Therefore, achieving richer, more durable, and more flexible optical anti-counterfeiting effects while ensuring concealment remains a critical technical challenge that urgently needs to be overcome in the field of electricity meter sealing. Summary of the Invention
[0005] To overcome the aforementioned shortcomings of existing technologies, this invention proposes a sealing structure for an energy meter with optical anti-counterfeiting features, along with its design and fabrication method. By doping a single material with two specific functional materials, a composite structure with more pronounced anisotropy is constructed. This sealing structure expands the spectral response range of the thin film, coupling a third characteristic color in addition to the original two colors, and significantly enhances color saturation and contrast by strengthening the local field effect. Simultaneously, the asymmetric orientation formed by the doped materials modulates the optical anisotropy of the thin film, making its color exhibit a significant angle dependence. The strong chemical bonding between the doped materials and the substrate, along with the dense passivation layer formed by the oxides of the doped materials, increases the adhesion strength of the thin film and improves its overall oxidation resistance. These characteristics collectively enable the anti-counterfeiting film to achieve significant multi-color switching and a wide-angle polarization response, greatly enhancing the recognizability and anti-counterfeiting capability of the anti-counterfeiting features while maintaining high concealment. The innovation lies in the fact that this energy meter seal combines high concealment, angle dependence, long-term cycle stability, and diverse color changes.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: An energy meter sealing structure with optical anti-counterfeiting features is disclosed. The sealing structure uses the sealing surface as a base and laser engraving technology is used to carve grooves of a certain depth with specific patterns (including specific graphics and characters) on the base as a mark. The mark is processed from bottom to top into a transition layer, a functional layer, and a protective layer. The transition layer, functional layer, and protective layer are combined into a multi-layer film structure, which serves as a thin-film mark with anti-counterfeiting features, resulting in an energy meter sealing structure with optical anti-counterfeiting features.
[0007] Furthermore, the color of the sealing structure of the electricity meter is determined by the overall thickness of the functional layer, transition layer, and protective layer combined, specifically: When viewed from a vertical (90°) elevation angle, the observed color is pink. To ensure consistency with the substrate's appearance color under vertical elevation angle conditions, the substrate material is dyed or sprayed to become pink, thus achieving a concealed marking effect. At elevation angles other than 90°, two scenarios emerge; details are as follows: Case 1: When the observation pitch angle is 0° to 49° or 81° to 90°, the multilayer film structure appears pink within any polarization angle range. The second scenario: When the observation pitch angle is between 50° and 80°, under polarization observation, the multilayer film structure exhibits three different colors within different polarization angle ranges. Specifically: within the polarization angle ranges of 0° to 50° and 150° to 180°, the multilayer film structure appears pink; within the polarization angle range of 50° to 115°, the multilayer film structure appears light gold; and within the polarization angle range of 115° to 150°, the multilayer film structure appears purple. The light gold and purple colors create a significant color difference from the pink of the substrate, thus highlighting the logo pattern under the corresponding polarization observation conditions. However, under other polarization angles and under conventional unpolarized light illumination conditions, the multilayer film structure always maintains the same color as the substrate (both are pink), making the logo unidentifiable. In other words, in the second case, when the observation pitch angle is between 50° and 80°, the multilayer film structure exhibits two colors different from the substrate color within the polarization angle range of 50°-115° and 115°-150°, highlighting the specific pattern after laser engraving. At other polarization angles, it remains consistent with the substrate color, and no specific pattern can be observed.
[0008] Furthermore, the substrate is made of plastic material, selected from acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate (PC) or polypropylene (PP), etc., with a thickness of 1-5cm and a width of 1-5cm.
[0009] Furthermore, the markings are processed using high-precision laser engraving technology. The core process parameters are as follows: the laser engraving machine is set with laser power adjusted to 20%-80% of the rated power, the engraving speed is set to 200-400mm / s, and the cumulative depth is achieved by setting the number of repeated scans to 8-16 times. At the same time, the pulse frequency is set to 20-50kHz, the line spacing is filled to 1-30μm, and the depth is 10-40μm.
[0010] Furthermore, the transition layer is made of ZnO material with a thickness of 100-300 nm.
[0011] Furthermore, the functional layer is a co-doped structure of the main color-changing material and ZnO and Al2O3; the main color-changing material is selected from WO3, MoO3 or GST, the doping ratio of ZnO is 1%-5%, and the doping ratio of Al2O3 is 1%-5%; the thickness of the functional layer is 10-30 μm. Here, the ZnO doping ratio refers to the mass percentage of ZnO in the functional layer, and the Al2O3 doping ratio refers to the mass percentage of Al2O3 in the functional layer.
[0012] Furthermore, the protective layer is a mixture of ZnO and Al2O3, wherein the mass percentage of ZnO is 60-80%, the mass percentage of Al2O3 is 10-30%, and the thickness is 100-300 nm.
[0013] A design method for a sealing structure of an electricity meter with optical anti-counterfeiting features, the design method comprising the following steps: The first step involves constructing a three-dimensional optical model of the electricity meter seal using FDTD simulation software, establishing the sealing structure including the substrate, marking, transition layer, functional layer, and protective layer. Then, the optical characteristics of each layer under plane wave incidence are calculated using the transfer matrix method (TFCalc) coupled to the vertical multilayer film region, including reflectivity, transmittance, and electric field distribution. Specifically: Discrete meshes are used for the substrate and markings to calculate and simulate the scattering and near-field distribution caused by the sidewalls of the grooves, thereby reducing the impact of abrupt edge changes. The mesh size of the discrete mesh is ≤λ / 20, where λ represents the wavelength of the incident light source during the simulation, which is taken as the visible light band, 400-700nm.
[0014] The thin film interference and polarization anisotropy responses are analyzed layer by layer using the transfer matrix method for the transition layer, functional layer, and protective layer. This overcomes the limitations of excessive computational cost of a single FDTD and the inability of a single transfer matrix to handle groove morphology, and achieves cross-scale optical coupling modeling of "macro-groove-micro-multilayer film".
[0015] The second step is to input the refractive index and absorptivity of the substrate, transition layer, functional layer, and protective layer in the visible light band. The third step is to input the thickness parameter ranges for the substrate, marking, transition layer, functional layer, and protective layer. Specifically: The ABS, PP, and PC materials corresponding to the substrate are in the cm range. The actual thickness and width of the substrate are 1-5cm. A marker with an S-shaped groove of 1-30 μm line width and 10-50 μm thickness is set in the substrate. The specific parameters are adjusted according to the actual substrate. The thickness of the groove corresponding to the marker is the sum of the thicknesses of the transition layer, functional layer and protective layer, so as to ensure that the multilayer film structure completely fills the marker groove and forms a flat upper surface.
[0016] The initial thickness of the transition layer is in the range of 10-500 nm. If the transition layer thickness is less than 100 nm, a continuous and dense structure cannot be formed on the substrate surface, the refractive index matching effect fails, and the chemical bonding density between the ZnO lattice and the substrate hydroxyl groups (Zn-OC) is insufficient, leading to unsatisfactory film adhesion strength. When the transition layer thickness exceeds 300 nm, cracks will form in the transition layer itself due to the accumulation of lattice stress in the thickness direction. Simultaneously, optical interference effects begin to interfere with the material's optical response, introducing additional reflection peaks and thus disrupting the expected color response. Therefore, the preferred thickness is 100 nm-300 nm. The initial thickness of the functional layer is in the range of 500 nm to 30 μm. Based on the comprehensive balance between optical interference and polarization anisotropy, the thickness of the functional layer should not be too thin, and the thickness of the multilayer film needs to be consistent with the thickness of the marking groove. Therefore, the thickness should be at least in the micrometer range. Within this thickness range, optical interference can produce a double-peak resonance covering the visible light band. Simultaneously, the asymmetric lattice orientation of the doped crystal optimizes the optical anisotropy coefficient, thus achieving three-stage color change at both the observation pitch and polarization angles. However, during simulation, a thickness below 10 μm results in insufficient interference order and weak anisotropy, while a thickness above 30 μm leads to increased surface scattering, decreased contrast, and exceeds the maximum thickness of the marking. Therefore, the optimal thickness of the functional layer is 10-30 μm. The initial thickness of the protective layer is 10-500 nm. When the thickness is below 100 nm, the pinhole density of the protective layer increases sharply, making it impossible to form a dense oxygen diffusion barrier. This prevents the low oxygen permeability characteristics of the Al2O3 component from being utilized, leading to easy oxidation of the film in humid and hot environments and a decrease in long-term cycling stability. Beyond 300 nm, the difference in thermal expansion coefficients between the protective layer and the functional layer causes the interfacial shear stress to exceed a critical value, making delamination and peeling likely during temperature cycling tests. Furthermore, an excessively thick protective layer weakens the polarization light extraction efficiency of the functional layer, reducing the color contrast between pale gold and purple. Therefore, the preferred thickness is 100-300 nm. The fourth step involves using FDTD simulation software combined with the transfer matrix method to calculate the reflectance spectral characteristics of the multilayer film structure within the polarization angle range of 0°-180° and the observation elevation angle range of 0°-90°. With maximizing color change contrast as the optimization objective, the thicknesses of the functional layer (10-30 μm), transition layer (100-300 nm), and protective layer (100-300 nm) are scanned, and an optimization function is defined. The objective function is optimized by weighted summation to simultaneously maximize the color change corresponding to the two color differences between the anti-counterfeiting label and the substrate at the target polarization angle, and minimize the color change corresponding to the color difference between the label and the substrate at non-target polarization angles. This achieves optimal color switching contrast while ensuring concealment. The wavelength difference and polarization extinction ratio of the reflectance spectral peaks are used as auxiliary constraints to ensure the final results at the corresponding observation elevation angles. It is determined that when the functional layer thickness is 10-30 μm and the transition and protective layer thicknesses are both 100-300 nm, the reflectance spectrum exhibits the best bimodal separation in the visible light band, and the polarization-dependent color switching is most significant.
[0017] Furthermore, the logo pattern is drawn using CorelDRAW or AutoCAD graphics software.
[0018] A method for preparing a sealing structure for an energy meter with optical anti-counterfeiting features, using magnetron sputtering, includes the following steps: Step 1: Pretreatment and functional layer deposition; Step 1.1, Pretreatment of target and substrate; The substrate materials are ABS, PP, and PC, typically white or transparent. The main color-changing material (WO3, MoO3, or GST) of the functional layer (purity ≥99.9%), ZnO, and Al2O3 targets are mounted on independent target positions in the multi-target magnetron sputtering system, with the target-substrate distance adjusted to 50–80 mm. Pre-sputter cleaning of the target surfaces is performed for 10–15 minutes to remove impurities. Simultaneously, the marked substrate is ultrasonically cleaned in isopropanol solution for 10–30 minutes (power 60–100 W), followed by drying with a nitrogen gun for 5–10 minutes (pressure 0.05–0.1 MPa) to ensure a clean, residue-free surface.
[0019] Step 1.2, Deposit the transition layer; A transition layer was deposited on the pretreated substrate using radio frequency magnetron sputtering. The chamber background vacuum was controlled to be ≤5.0×10⁻⁶. -4 Pa, argon gas flow rate 10–20 sccm, sputtering power set to 80–120 W, working pressure maintained at 0.3–0.6 Pa, deposition time adjusted according to the required thickness, final transition layer thickness 100–300 nm.
[0020] Step 1.3, Deposit the functional layer; Switch to multi-target co-sputtering mode, simultaneously activating the host color-changing material (WO3, MoO3, or GST), ZnO, and Al2O3 targets for the functional layer. The host color-changing material target power is set to 80–120 W, the ZnO target power to 60–100 W, and the Al2O3 target power to 20–40 W. The argon flow rate is maintained at 10–20 sccm, the working pressure at 0.3–0.6 Pa, a pulsed bias voltage of -50 V to -100 V is applied, and the magnetic field strength is adjusted to 0.1 T to 0.3 T. By controlling the deposition time, the final thickness of the functional layer is achieved to 10–30 μm, forming a co-doped structure with 1%–5% ZnO and 1%–5% Al2O3 doping ratios.
[0021] Step 1.4, Deposit a protective layer; The main color-changing material target was turned off, and only ZnO and Al2O3 dual-target co-sputtering was retained. The argon flow rate was set to 10–20 sccm, the ZnO target power to 60–100 W, the Al2O3 target power to 20–40 W, the working pressure to 0.3–0.6 Pa, and the deposition time to be adjusted according to the required thickness. The final protective layer achieved a ZnO mass percentage of 80%, an Al2O3 mass percentage of 20%, and a thickness of 100–300 nm, preventing oxidation of the functional layer and improving environmental stability.
[0022] Through steps 1.1 to 1.4 above, a transition layer, a functional layer, and a protective layer are sequentially formed above the marked area in the substrate, constituting a complete multilayer film structure. This structure possesses basic optical anti-counterfeiting properties after deposition, but it contains residual stress and amorphous components, requiring subsequent annealing and encapsulation treatments to optimize its performance.
[0023] Step 2: Thin film post-processing and encapsulation; Step 2.1, in-situ annealing optimization; After deposition, maintain the substrate temperature at 200–300℃ for 30 minutes to eliminate internal stress and promote oriented grain growth. After cooling to <100℃, remove the complete seal by breaking the vacuum.
[0024] Step 2.2, edge sealing and encapsulation; An epoxy resin edge sealing layer is applied to enhance film adhesion and environmental stability, forming a complete sealing structure for the electricity meter.
[0025] The beneficial effects of this invention are: (1) High concealment: This invention achieves extremely high observation concealment through the combination of a multi-layer film structure (composed of a transition layer, a functional layer, and a protective layer) and the marking. Under conventional observation conditions (i.e., arbitrary observation pitch angle and non-polarized light illumination), the color of the multi-layer film structure is completely consistent with the base color (pink), and the key dynamic optical information is completely hidden, making it impossible to identify or copy by the naked eye or ordinary shooting equipment. Only within specific observation pitch angles (50°-80°) and specific polarization angles (50°-115° and 115°-150°) does the multi-layer film structure exhibit light gold and purple respectively, thus highlighting the marking pattern. This feature effectively eliminates traditional counterfeiting methods such as digital reproduction and photocopying, upgrading the anti-counterfeiting feature from "visible" to "controllable visible," significantly enhancing the initiative and confidentiality of anti-counterfeiting.
[0026] (2) Angle Dependence: Based on the optical interference characteristics and polarization anisotropy design of the multilayer film structure, the color rendering effect of this invention exhibits a strict dependence on the observation pitch angle and polarization angle. It only displays a light gold color when the observation pitch angle is between 50° and 80° and the polarization angle is between 50° and 115°, and a purple color when the polarization angle is between 115° and 150°. At other polarization angles and observation pitch angles, it maintains a pink color consistent with the substrate. This extreme sensitivity to observation conditions stems from the asymmetric lattice orientation induced by ZnO and Al2O3 added to the functional layer, constituting a unique and difficult-to-replicate anti-counterfeiting property.
[0027] (3) Long-term cycle stability: The multilayer film structure used in this invention achieves multiple long-term stability mechanisms through a dense inorganic gradient structure formed by multi-target co-sputtering. First, the passivation performance of the protective layer effectively blocks oxygen and water vapor penetration, inhibiting the oxidation degradation of the functional layer; second, the transition layer (ZnO) forms a strong chemical bond (Zn-OC) with the substrate, which, combined with the buffering effect of the protective layer, significantly improves the adhesion strength of the film, enabling it to withstand repeated bending, friction, and drastic changes in environmental temperature and humidity. Compared with fluorescent materials, this inorganic composite film has toughness, aging resistance, and oxidation resistance, providing long-term material protection for anti-counterfeiting.
[0028] (4) Diverse Color Variation: The multilayer film structure of this invention, through the co-doping of ZnO and Al2O3 in the functional layer, constructs significant optical anisotropy, breaking through the limitation of traditional optical color-changing materials that only change two colors. At observation pitch angles of 50°-80°, three colors can be switched with the polarization angle: "pink - light gold - purple", broadening the dimensions of visual verification. At the same time, the refractive index matching design of the transition layer and the protective layer enhances the polarization-dependent reflection modulation, increasing the color shift by about 40% compared to a single material system, and making the color contrast more sensitive with the change of viewing angle. This feature not only increases the density of anti-counterfeiting information, but also significantly improves the difficulty of counterfeiting, providing a high-security solution for long-term reliable optical anti-counterfeiting.
[0029] In summary, this invention, through a combination of innovative optical design, algorithm optimization, and process optimization, successfully solves the technical bottlenecks in anti-counterfeiting identification and tamper protection of electricity meter seals, providing a novel design for the security protection of smart grid metering equipment that combines high concealment, angle dependence, long-term cycle stability, and diverse color changes. Attached Figure Description
[0030] Figure 1 This is a cross-sectional view of the seal structure of an electricity meter with optical anti-counterfeiting features.
[0031] Figure 2 This is a top view of the seal structure of an electricity meter with optical anti-counterfeiting features.
[0032] In the diagram: 1. Base; 2. Marker; 3. Transition layer; 4. Functional layer; 5. Protective layer. Detailed Implementation
[0033] The present invention will be further described below with reference to specific implementation examples.
[0034] Example 1 A design method for a sealing structure of an energy meter with optical anti-counterfeiting features includes the following steps: The first step involves constructing a three-dimensional optical model of the electricity meter seal using FDTD simulation software, establishing the sealing structure of the electricity meter including substrate 1, marking 2, transition layer 3, functional layer 4, and protective layer 5. Then, the optical properties of each layer, such as reflectivity, transmittance, and electric field distribution, under plane wave incidence are calculated using the transfer matrix method (TFCalc) coupled to the vertical multilayer film region. Specifically: Discrete meshes were used for the structures of base 1 and marker 2 to calculate and simulate the scattering and near-field distribution caused by the sidewalls of the groove, thereby reducing the impact of abrupt edge changes. The thin film interference and polarization anisotropy responses were analyzed layer by layer for transition layer 3, functional layer 4, and protective layer 5 using the transfer matrix method. This overcomes the limitations of excessive computational cost of a single FDTD and the inability of a single transfer matrix to handle groove morphology, and achieves cross-scale optical coupling modeling of "macro-groove-micro-multilayer film".
[0035] The second step is to input the refractive index and absorptivity of substrate 1, transition layer 3, functional layer 4, and protective layer 5 in the visible light band. The third step is to input the thickness parameter ranges for substrate 1, identifier 2, transition layer 3, functional layer 4, and protective layer 5. Specifically: The ABS, PP, and PC materials corresponding to substrate 1 are in the cm range. The actual thickness and width of substrate 1 are 1-5 cm. A mark 2 is provided in the substrate 1, with an S-shaped groove having a line width of 10 μm and a thickness of 40 μm. The thickness of the groove corresponding to mark 2 is the sum of the thicknesses of the transition layer 3, the functional layer 4, and the protective layer 5, so as to ensure that the multilayer film structure completely fills the groove of mark 2 and forms a flat upper surface.
[0036] The initial thickness of the transition layer 3 is in the range of 10-500 nm. If the thickness of the transition layer 3 is less than 100 nm, a continuous and dense structure cannot be formed on the surface of the substrate 1, the refractive index matching effect fails, and the chemical bonding density (Zn-OC) between the ZnO lattice and the hydroxyl groups of the substrate 1 is insufficient, resulting in insufficient film adhesion strength. When the thickness of the transition layer 3 exceeds 300 nm, cracks will form in the transition layer 3 itself due to the accumulation of lattice stress in the thickness direction. Simultaneously, optical interference effects begin to interfere with the optical response of the material, introducing additional reflection peaks and thus disrupting the expected color response. Therefore, the preferred thickness is 150 nm. The initial thickness of functional layer 4 ranges from 500 nm to 30 μm. Based on the comprehensive balance between optical interference and polarization anisotropy, the thickness of functional layer 4 should not be too thin, and the thickness of the multilayer film needs to be consistent with the thickness of the groove in mark 2. Therefore, the thickness should be at least in the micrometer range. Within this thickness range, optical interference can generate a double-peak resonance covering the visible light band. At the same time, the asymmetric lattice orientation of the doped crystal optimizes the optical anisotropy coefficient, thereby achieving three-segment color change at the observation pitch angle and polarization angle. Meanwhile, during the simulation, when the thickness is less than 10 μm, there will be insufficient interference order and weak anisotropy. When it is greater than 30 μm, surface scattering increases and contrast decreases, and it exceeds the maximum thickness of mark 2. Therefore, the thickness of functional layer 4 is preferably 29.6 μm.
[0037] The initial thickness of the protective layer 5 is in the range of 10-500 nm. When the thickness of the protective layer 5 is less than 100 nm, the pinhole density of the protective layer increases sharply, making it impossible to form a dense oxygen diffusion barrier. The low oxygen permeability characteristics of the Al2O3 component cannot be utilized, and the film is prone to oxidation in a humid and hot environment, resulting in a decrease in long-term cycling stability. When the thickness exceeds 300 nm, the difference in the coefficient of thermal expansion between the protective layer 5 and the functional layer 4 causes the interfacial shear stress to exceed the critical value, making it prone to delamination and peeling during temperature cycling tests. At the same time, an excessively thick protective layer will weaken the polarization light extraction efficiency of the functional layer 4 and reduce the color contrast between pale gold and purple. Therefore, the thickness is preferably 250 nm.
[0038] The fourth step involves using FDTD simulation software combined with the transfer matrix method to calculate the reflectance spectral characteristics of the multilayer film structure within the polarization angle range of 0°-180° and the observation elevation angle range of 0°-90°. With maximizing color change contrast as the optimization objective, the thicknesses of functional layer 4, transition layer 3, and protective layer 5 are scanned, and an optimization function is defined. The objective function is optimized by weighted summation, simultaneously maximizing the color change corresponding to the two color differences between the anti-counterfeiting label and the substrate at the target polarization angle, and minimizing the color change corresponding to the color difference between the label and the substrate at non-target polarization angles. This achieves optimal color switching contrast while ensuring concealment. The wavelength difference and polarization extinction ratio of the reflectance spectral peaks are used as auxiliary constraints to ensure the final results at the corresponding observation elevation angles. It is determined that when the thickness of functional layer 4 is 29.6 μm, transition layer 3 is 150 nm, and protective layer 5 is 250 nm, the reflectance spectrum exhibits the best bimodal separation in the visible light band, and the polarization-dependent color switching is most significant.
[0039] Furthermore, the pattern of the logo 2 is drawn using CorelDRAW or AutoCAD graphics software.
[0040] This embodiment also provides a method for preparing a sealing structure for an energy meter with optical anti-counterfeiting features, which is prepared using a magnetron sputtering process and includes the following steps: Step 1: Pretreatment and functional layer deposition; Step 1.1, Pretreatment of target and substrate; The substrate 1 is made of ABS, PP, or PC materials, typically white or transparent. The corresponding colors of the multilayer film are added to the substrate 1 through spraying or dyeing. The main color-changing material (WO3, MoO3, or GST) of the functional layer 4 (purity ≥99.9%), along with ZnO and Al2O3 targets, are mounted on independent target positions in the multi-target magnetron sputtering system, with the target-substrate distance adjusted to 60mm. Pre-sputtering cleaning of the target surfaces is performed for 12 minutes to remove impurities. Simultaneously, the substrate 1, marked with "2", is ultrasonically cleaned in isopropanol solution for 20 minutes (80W power), followed by drying with a nitrogen gun for 7 minutes (0.08MPa pressure) to ensure a clean, residue-free surface.
[0041] Step 1.2, Deposit the transition layer; A transition layer 3 was deposited on the pretreated substrate 1 using radio frequency magnetron sputtering. The chamber background vacuum was controlled to be ≤5.0×10⁻⁶. -4 Pa, argon gas flow rate 15 sccm, sputtering power set to 100W, working pressure maintained at 0.4Pa, deposition time adjusted according to the required thickness, final transition layer 3 thickness 150nm.
[0042] Step 1.3, Deposit the functional layer; The process was switched to multi-target co-sputtering mode, simultaneously activating the host color-changing material (WO3, MoO3, or GST) target, ZnO target, and Al2O3 target for functional layer 4. The power of the host color-changing material target was set to 100W, the ZnO target power to 80W, and the Al2O3 target power to 25W. The argon flow rate was maintained at 15 sccm, the working pressure at 0.4 Pa, a -70V pulsed bias was applied, and the magnetic field strength was adjusted to 0.2T. By controlling the deposition time, the final thickness of functional layer 4 was achieved to 29.6 μm, forming a co-doped structure with a color-changing material doping ratio of 1.5% ZnO and 3% Al2O3.
[0043] Step 1.4, Deposit a protective layer; The main color-changing material target was turned off, and only ZnO and Al2O3 dual-target co-sputtering was retained. The argon flow rate was set to 15 sccm, the ZnO target power was 80W, the Al2O3 target power was 25W, the working pressure was 0.4 Pa, and the deposition time was adjusted according to the required thickness. The final protective layer 5 achieved a ZnO mass percentage of 80%, an Al2O3 mass percentage of 20%, and a thickness of 250 nm, preventing the oxidation of the functional layer 4 and improving environmental stability.
[0044] Through steps 1.1 to 1.4 above, a transition layer 3, a functional layer 4, and a protective layer 5 are sequentially formed above the marking area 2 in the substrate 1, constituting a complete multilayer film structure. This structure possesses basic optical anti-counterfeiting properties after deposition, but it contains residual stress and amorphous components, requiring subsequent annealing and encapsulation treatments to optimize its performance.
[0045] Step 2: Thin film post-processing and encapsulation; Step 2.1, in-situ annealing optimization; After deposition, maintain the substrate temperature at 250℃ for 30 minutes to eliminate internal stress and promote directional grain growth. After cooling to <100℃, remove the complete seal by breaking the vacuum.
[0046] Step 2.2, edge sealing and encapsulation; An epoxy resin edge sealing layer is applied to enhance film adhesion and environmental stability, forming a complete sealing structure for the electricity meter.
[0047] The specific sealing structure of the electricity meter provided in this embodiment is as follows: An energy meter sealing structure with optical anti-counterfeiting features is disclosed. The sealing structure uses the sealing surface as a base 1. After laser engraving technology is used to engrave a groove mark 2 with a certain depth and a specific pattern (including specific graphics and characters) on the base 1, the structure consists of a transition layer 3, a functional layer 4, and a protective layer 5 from bottom to top. The transition layer 3, functional layer 4, and protective layer 5 form a multi-layer film structure, which serves as a thin-film anti-counterfeiting mark, thus obtaining the energy meter sealing structure with optical anti-counterfeiting features.
[0048] In this embodiment, the color of the electricity meter sealing structure is determined by the overall thickness of the combined functional layer 4 (29.6 μm thick), transition layer 3 (150 nm thick), and protective layer 5 (250 nm thick), specifically: When viewed from a vertical (90°) elevation angle, the observed color is pink. To ensure that the color matches the appearance of the base 1 under vertical elevation angle conditions, the base 1 material is dyed and sprayed to turn pink, thus achieving the concealment effect of the marking 2. At elevation angles other than 90°, two scenarios emerge; details are as follows: Case 1: When the observation pitch angle is 0° to 49° or 81° to 90°, the multilayer film structure appears pink within any polarization angle range. The second scenario: When the observation pitch angle is between 50° and 80°, under polarization observation, the multilayer film structure exhibits three different colors within different polarization angle ranges. Specifically: within the polarization angle ranges of 0° to 50° and 150° to 180°, the multilayer film structure appears pink; within the polarization angle range of 50° to 115°, the multilayer film structure appears light gold; and within the polarization angle range of 115° to 150°, the multilayer film structure appears purple. Among these, the light gold and purple colors show a significant color difference from the pink of substrate 1, thus highlighting the pattern of mark 2 under the corresponding polarization observation conditions. However, under other polarization angles and under conventional unpolarized light illumination conditions, the multilayer film structure always maintains the same color as substrate 1 (both are pink), making mark 2 unidentifiable.
[0049] The above-described Embodiment 1 merely illustrates the implementation of the present invention, but should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention.
Claims
1. A sealing structure for an electricity meter with optical anti-counterfeiting features, characterized in that, The sealing structure of the electricity meter uses the sealing surface as a base (1). A groove with a specific pattern of a certain depth is engraved on the base (1) using laser engraving technology as a mark (2). The mark (2) is processed from bottom to top into a transition layer (3), a functional layer (4), and a protective layer (5). The transition layer (3), the functional layer (4), and the protective layer (5) are combined into a multi-layer film structure, which serves as a thin-film mark with anti-counterfeiting features. Finally, an electricity meter sealing structure with optical anti-counterfeiting features is obtained. The transition layer (3) is made of ZnO material with a thickness of 100-300 nm; the functional layer (4) is a co-doped structure of the main color-changing material and ZnO and Al2O3 with a thickness of 10-30 μm; the protective layer (5) is a mixed material of ZnO and Al2O3 with a thickness of 100-300 nm. The color of the multilayer membrane structure is determined by the overall thickness of the functional layer (4), transition layer (3), and protective layer (5). Specifically: Under a 90° observation pitch angle, the observation color of the multilayer membrane structure is pink; by means of dyeing and spraying, the substrate (1) material is changed to pink to achieve the concealment effect of the mark (2); At other different observation pitch angles, two types of situations emerge; as detailed below: Case 1: When the observation pitch angle is 0° to 49° or 81° to 90°, the multilayer film structure appears pink within any polarization angle range. The second scenario: When the observation pitch angle is between 50° and 80°, under polarization observation, the multilayer film structure exhibits three different colors within different polarization angle ranges; specifically: In the polarization angle range of 0° to 50° and 150° to 180°, the multilayer film structure appears pink and the markings cannot be identified (2); Within a polarization angle range of 50° to 115°, the multilayer film structure appears light gold and can be identified (2); In the polarization angle range of 115° to 150°, the multilayer film structure appears purple, which can be used to identify the mark (2).
2. The sealing structure of an energy meter with optical anti-counterfeiting markings according to claim 1, characterized in that, In the sealing structure of the energy meter: The substrate (1) is made of plastic material with a thickness of 1-5cm; The logo (2) is processed using high-precision laser engraving technology.
3. The sealing structure of an energy meter with optical anti-counterfeiting markings according to claim 2, characterized in that, In the sealing structure of the energy meter: The substrate (1) is selected from acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate (PC), or polypropylene (PP); The processing parameters of the mark (2) are as follows: laser engraving machine, laser power is adjusted to 20%-80% of the rated power, engraving speed is set to 200-400mm / s, and cumulative depth is achieved by setting the number of repeated scans to 8-16 times. At the same time, the pulse frequency is set to 20-50kHz, the line spacing is filled to 1-30μm, and the depth is 10-40μm.
4. The sealing structure of an energy meter with optical anti-counterfeiting markings according to claim 3, characterized in that, In the sealing structure of the energy meter: In the functional layer (4), the main color-changing material is selected from WO3, MoO3 or GST material, the doping ratio of ZnO is 1%-5%, and the doping ratio of Al2O3 is 1%-5%; wherein, the doping ratio of ZnO refers to the mass percentage of ZnO in the functional layer (4), and the doping ratio of Al2O3 refers to the mass percentage of Al2O3 in the functional layer (4); In the protective layer (5), the mass percentage of ZnO is 60-80% and the mass percentage of Al2O3 is 10-30%.
5. A design method for a sealing structure of an energy meter with optical anti-counterfeiting markings as described in any one of claims 1-4, characterized in that, The design method Includes the following steps: The first step is to construct a three-dimensional optical model of the electricity meter seal using FDTD simulation software, and establish the electricity meter seal structure including the base (1), the mark (2), the transition layer (3), the functional layer (4), and the protective layer (5); and to calculate the optical characteristics of each layer structure under plane wave incident by coupling the transmission matrix method in the vertical multilayer film region, including reflectivity, transmittance, and electric field distribution. The second step is to input the refractive index and absorptivity of the substrate (1), transition layer (3), functional layer (4), and protective layer (5) in the visible light band. The third step is to input the thickness parameter ranges of the substrate (1), identifier (2), transition layer (3), functional layer (4), and protective layer (5); The fourth step is to use FDTD simulation software combined with the transfer matrix method to calculate the reflection spectral characteristics of the multilayer film structure within the range of polarization angles from 0° to 180° and observation pitch angles from 0° to 90°; and to determine that when the thickness of the functional layer (4) is 10-30 μm and the thicknesses of the transition layer (3) and the protective layer (5) are both 100-300 nm, the reflection spectrum has the best bimodal separation and polarization-dependent color switching in the visible light band.
6. The design method of a sealing structure for an energy meter with optical anti-counterfeiting markings according to claim 5, characterized in that, In the first step: a discrete mesh is used for the substrate (1) and the marker (2) to calculate the scattering and near-field distribution caused by the sidewall of the groove, thereby reducing the impact of abrupt edge changes; wherein, the mesh size of the discrete mesh is ≤λ / 20, where λ represents the wavelength of the incident light source during simulation; the thin film interference and polarization anisotropy response are analyzed layer by layer for the transition layer (3), functional layer (4), and protective layer (5) using the transfer matrix method, thereby realizing cross-scale optical coupling modeling of macroscopic groove-microscopic multilayer film.
7. The design method of a sealing structure for an energy meter with optical anti-counterfeiting markings according to claim 6, characterized in that, In the third step: The ABS, PP, and PC materials corresponding to the substrate (1) are in the cm range. The actual thickness and width of the substrate (1) are 1-5 cm. A mark (2) corresponding to a groove with a line width of 1-30μm and a thickness of 10-50μm is set in the substrate (1); the thickness of the groove corresponding to the mark (2) is the sum of the thicknesses of the transition layer (3), the functional layer (4) and the protective layer (5); The initial thickness of the transition layer (3) ranged from 10 to 500 nm. Through simulation, it was found that when the thickness of the transition layer (3) was less than 100 nm, a continuous and dense structure could not be formed on the surface of the substrate (1), and the refractive index matching effect failed. When the thickness of the transition layer (3) exceeded 300 nm, cracks were generated in the transition layer (3) due to the accumulation of lattice stress in the thickness direction, and additional reflection peaks were introduced. Therefore, through simulation, the thickness of the transition layer (3) was finally determined to be 100 nm to 300 nm. The initial range of the thickness of the functional layer (4) is 500nm-30μm; through simulation, the three-stage color change under the observation pitch angle and polarization angle is realized; and during the simulation process, when the thickness is less than 10μm, the interference order is insufficient and the anisotropy is weak, and when it is greater than 30μm, the surface scattering increases and the contrast decreases, and it exceeds the maximum thickness of the mark (2). Therefore, the thickness of the functional layer (4) is finally determined to be 10-30μm through simulation. The initial range of the thickness of the protective layer (5) is 10-500nm. Through simulation, it is found that when the thickness of the protective layer (5) is less than 100nm, a dense oxygen diffusion barrier cannot be formed. When it exceeds 300nm, the protective layer (5) and the functional layer (4) are prone to delamination and peeling during temperature cycling tests. At the same time, the excessively thick protective layer reduces the color contrast between light gold and purple. Therefore, the thickness of the protective layer (5) is finally determined to be 100-300nm through simulation.
8. The design method of a sealing structure for an energy meter with optical anti-counterfeiting markings according to claim 7, characterized in that, In the fourth step: With maximizing the contrast of color change as the optimization objective, the thickness of the functional layer (4), the thickness of the transition layer (3), and the thickness of the protective layer (5) are scanned, and an optimization function is defined. The optimization objective function is optimized by weighted summation, which simultaneously maximizes the color change corresponding to the two color differences between the anti-counterfeiting mark and the substrate under the target polarization angle, and minimizes the color change corresponding to the color difference between the mark and the substrate under the non-target polarization angle, thereby achieving the best color switching contrast while ensuring concealment. At the same time, the wavelength difference of the reflection spectrum peak and the polarization extinction ratio are used as auxiliary constraints.
9. A method for preparing a sealing structure for an energy meter with optical anti-counterfeiting features as described in any one of claims 1-4, characterized in that, The fabrication process employs magnetron sputtering and includes the following steps: Step 1: Pretreatment and functional layer deposition; Step 1.1, Pretreatment of target and substrate (1); The main color-changing material target, ZnO target and Al2O3 target of the functional layer (4) with a purity ≥99.9% were respectively installed in the independent target positions of the multi-target source magnetron sputtering system, and the target-substrate distance was adjusted to 50–80 mm; the surface impurities of each target were pre-sputtered and cleaned for 10–15 minutes; at the same time, the substrate (1) with the mark (2) was ultrasonically cleaned and then dried with nitrogen. Step 1.2, depositing the transition layer (3); A transition layer (3) was deposited on the pretreated substrate (1) using radio frequency magnetron sputtering mode. The thickness of the transition layer (3) was 100–300 nm. Step 1.3, depositing the functional layer (4); Switch to multi-target co-sputtering mode and simultaneously turn on the main color-changing material target, ZnO target and Al2O3 target of functional layer (4); wherein, the power of the main color-changing material target is set to 80-120W, the power of ZnO target is 60-100W and the power of Al2O3 target is 20-40W; set the argon flow rate, adjust the working gas pressure and magnetic field strength, and apply pulse bias voltage; by controlling the deposition time, form a co-doped structure of color-changing material doping ratio and ZnO and Al2O3, and the thickness of functional layer (4) is 10-30μm; Step 1.4, deposit protective layer (5); Turn off the main color-changing material target and only retain the ZnO and Al2O3 dual-target co-sputtering; set the argon flow rate and working pressure, ZnO target power 60–100W, Al2O3 target power 20–40W, and adjust the deposition time according to the required thickness to obtain a protective layer with a thickness of 100–300nm (5). Through steps 1.1 to 1.4, a transition layer (3), a functional layer (4), and a protective layer (5) are sequentially formed in the substrate (1) and the marking (2) to form a complete multilayer membrane structure; Step 2: Thin film post-processing and encapsulation; Step 2.1, in-situ annealing optimization; After deposition, the substrate (1) temperature was maintained at 200–300℃ for 30 minutes, and then cooled to <100℃ before being removed from the vacuum. Step 2.2, edge sealing and encapsulation; A sealing layer is applied to the edges to form a sealing structure for the electricity meter.
10. The method for preparing the sealing structure of the energy meter with optical anti-counterfeiting mark according to claim 9, characterized in that, In the preparation method: In step 1.2, the background vacuum of the control chamber is controlled to be ≤5.0×10⁻⁶. -4 Pa, argon gas flow rate 10–20 sccm, sputtering power set to 80–120 W, working pressure maintained at 0.3–0.6 Pa, deposition time adjusted according to the required thickness; In step 1.3, the argon flow rate is maintained at 10–20 sccm, the working pressure is 0.3–0.6 Pa, a pulse bias voltage of -50V to -100V is applied, and the magnetic field strength is 0.1T to 0.3T; In step 1.4, the argon flow rate is set to 10–20 sccm and the working pressure is set to 0.3–0.6 Pa. In step 2.2, the sealing layer material is epoxy resin.
Citation Information
Patent Citations
Ultraviolet fluorescent anti-counterfeiting film based on multilayer optical variability and preparation method of ultraviolet fluorescent anti-counterfeiting film
CN120082085A
Electric energy meter seal
CN219676116U
Dynamic anti-counterfeit label based on magnetic control birefringence effect and preparation and verification method thereof
CN121505983A
Color-changing anti-counterfeiting film and electronic product
CN212208736U